Avaliação de neoplasias mamárias malignas felinas quanto aos aspectos histopatológicos e à expressão imuno- histoquímica de Ki-67 e Caspase 3 clivada - Silva, Millena Nogueira Seabra da (2010)
Mammary neoplasm is the third most common cancer in feline, with most of the time a malignant behavior. For a diagnostic evaluation, prognosis and therefore the direction of a medical-surgical conduct appropriate classification is an essential characteristic. But often this classification is difficult, and used other techniques as an aid. Specialized techniques such as immunohistochemistry, to evaluate cell proliferation and apoptosis can serve as a basis for the diagnosis and prognosis. The application of these parameters helps comparative studies of feline mammary carcinogenesis and human. Thus, this study evaluated the hypothesis that the feline malignant mammary tumors have high expression of Ki-67 and cleaved caspase 3. The main objective was to evaluate the anatomic-pathological features and expression of Ki-67 and cleaved caspase-3 in malignant breast neoplasms domestic cats by linking the results of histopathology and immunohistochemistry. A total of 30 cases of mammary tumors in cats. The material was fixed in buffered formalin 10% and subsequently processed and embedded in paraffin. The tumors were classified according to World Health Organization, through histopathological examination of samples stained with hematoxylin and eosin. The reaction of immunohistochemistry was performed with the primary antibodies anti-Ki-67 and anticaspase 3. Most animals were classified as mixed breed cats, with a mean age of 10.43 years. Microscopically, we observed the presence of hyperchromatic nucleus, evident nucleoli, moderate pleomorphism and mitotic figures. In the cases studied, the neoplastic cells showed pattern-forming tubular, papillary, cystic and / or solid. Of the 30 samples were observed one case of tubulo-papillary adenocarcinoma with squamous differentiation, two cases of cystic tubular adenocarcinomas, five cases of tubular adenocarcinomas, papillary cystic, five cases of solid tubular adenocarcinomas, eight cases of tubular adenocarcinomas, papillary and nine cases of simple tubular adenocarcinomas. In three cases (3/13) showed regional lymph node metastasis. In nine cases (9/24), the surgical margins were invaded by neoplastic cells in two cases (2/24) there was invasion of muscle tissue and in one case (1/24) there was invasion to adipose tissue. In feline malignant mammary tumors was studied immunoreactivity of anti-Ki-67 and anti-cleaved Caspase 3, but there was no positive correlation between them. Although few studies with feline mammary tumors, mainly correlating the proliferative activity and apoptotic tumor. Through this study, we analyze the behavior histopathological and immunohistochemical of feline malignant mammary neoplasms. However, there is a need for more research to try to better understand tumor behavior and thus achieve a more accurate diagnosis